The Effect of Additional Dead Space on Respiratory Exchange Ratio and Carbon Dioxide Production Due to Training - Smolka, Lukasz (Asist Group, 2014)
The purpose of the study was to investigate the effects of implementing additional respiratory dead space during cycloergometry-based aerobic training. The primary outcome measures were respiratory exchange ratio (RER) and carbon dioxide production (VCO(2)). Two groups of young healthy males: Experimental (Exp, n = 15) and Control (Con, n = 15), participated in this study. The training consisted of 12 sessions, performed twice a week for 6 weeks. A single training session consisted of continuous, constant-rate exercise on a cycle ergometer at 60% of VO(2)max which was maintained for 30 minutes. Subjects in Exp group were breathing through additional respiratory dead space (1200ml), while subjects in Con group were breathing without additional dead space. Pre-test and two post-training incremental exercise tests were performed for the detection of gas exchange variables. In all training sessions, pCO(2) was higher and blood pH was lower in the Exp group (p < 0.001) ensuring respiratory acidosis. A 12-session training program resulted in significant increase in performance time in both groups (from 17”29 ± 1”31 to 18”47 ± 1”37 in Exp; p=0.02 and from 17”20 ± 1”18 to 18”45 ± 1”44 in Con; p = 0.02), but has not revealed a significant difference in RER and VCO(2) in both post-training tests, performed at rest and during submaximal workload. We interpret the lack of difference in post-training values of RER and VCO(2) between groups as an absence of inhibition in glycolysis and glycogenolysis during exercise with additional dead space.